Digital Literacy as An Effort to Build National Resilience In Defending the Country in the Digital Field - Anak Agung Mayra Candra Dyanggi; Naufal Islam; Riantodi Rian (Journal of Digital Law and Policy, 2022)
Technology has a huge impact on human life today. With the internet, humans are easy to dig up various information and almost entirely involve the internet as a medium to facilitate work. Over time, the internet and technology are growing and more information we can get, be it false information or real information. In this digital era, many people are not responsible for using the internet and digital media to spread hoaxes, provocative content, and other anti-Pancasila bullying content . This can lead to division and collapse of the integrity of the country. So it takes awareness in us to be digitally literate wisely.